Enhancing creativity through PjBL-STEAM equipped biogeochemical cycle educational kit on ecosystem materials in junior high school - Dina Febrianti; Erti Hamimi (Research and Development in Education (RaDEn), 2024)
The 21st Century learning requires students to have innovative and creative abilities. In supporting the learning process, the project-based learning model is used through the STEAM approach. This study aimed to develop PjBL-STEAM-based aquascape biogechemical cycle edukit on ecosystem material that are valid, practical, and effective to practice creative thinking skills. This development research used the ADDIE model including: 1) analyze; 2) design; 3) develop; 4) implement; 5) evaluate. Quantitative data was obtained from the value given by the validator, the results of the practicality tests of teachers and students, as well as the results of effectiveness through pretest and posttest questions. Meanwhile, qualitative data was obtained from teacher interview, comments, and suggestions provided by the validator and the teacher on each indicator in the instrument. Data collection techniques was conducted through interviews, questionnaires, and tests. The data analysis was carried out using percentage analysis and qualitative descriptive. The results of the material validation were 98% while the media validation were 94.25%. The results of the teacher's practicality test were 100% while students were 89%. The results of pretest and posttest showed a difference. The mean results of the N-Gain score for each indicator were categorized as medium with the highest increase results, namely the elaboration indicator and the lowest increase in the flexibility indicator. Based on these results, it can be concluded that the PjBL-STEAM-based aquascape biogeochemical cycle education is very valid, practical, and effective to be use in 7th graders in ecosystem material to train the creative thinking skills.